Você está na página 1de 80

1 a

X Y Z

1 2

1 a

13

1 a

N

2 a

n i

n i

n

f i n i n f i

f ac

n i

f i

f i × 100

f ac

n

(12, 2), (15, 3), (17, 1), (18, 4), (19, 1) (20, 1)

1 o

 

k = n

k =

1 + 3, 3 × log(n)

k n

A T ot = x max´

x m ´

in

x max´ x m ´ in

h =

A T ot

k

l i − |L i l i i sima L i

l i |−L i l i isima L i

1

2

P Md = n+1 n P Md

P 1 Md = n P2 Md = n + 1 n

2

2

2

M d M d(X)

2

mediana

n = 5

P Md = n+1

= 5+1

2

= 3 M d = 2

2

2 3 dois valores centrais
2
3
dois
valores
centrais

n = 6 P 1 Md = n = 6 = 3 P2 Md = n + 1 =

2

2

2

3 + 1 = 4

Md = x P 1Md + x P 2Md

2 + 3

=

2 2

= 2, 5.

1 P Md = n

2

P Md P Md

P Md P Md P Md + 1

P Md = n = 2 5 = 2, 5 P Md = 3 Md = 2

2

2

P Md = n = 6 = 3

P Md = 3 P Md +1 =

3 + 1 = 4

2

2

Md = x P 1Md + x P 2Md

2

=

2 + 3

2

= 2, 5.

M o M o (X)

1

M o = 2

1 2 2 3 5 5 M o = 2 M o = 5

5

2

2

3

=

(n)

Me Me(X) x

Me(X) = x =

(n) = 1 + 2 + 2 + 3 + 5

5

= 2, 6.

, x k k X

x 1 , x 2 ,

Me(X) = x = x 1 + x 2 +

k

+ x k

= 1

k

k

i=1

x i

n x 1 n 1 x 2 n 2 x k n k X

Me(X) = x = x 1 .n 1 + x 2 .n 2 +

n

+

x k .n k

= 1

n

=

=

k

i=1

k

i=1

k

i=1

x i .n i

x i . n i

n

x i .f i .

n i x i

n = i=1 n i

f i x i

k

1

2

2

3

5

Me(X) = x = 1

i • f i x i k 1 2 2 3 5 Me ( X )

n

k

i=1

x i .n i =

1

6 (1 × 1 + 2 × 2 + 3 × 1 + 5 × 2) = 18

6

5

= 3.

S

4, 00| − 8, 00 8, 00| − 12, 00 12, 00| − 16, 00 16, 00| − 20, 00 20, 00| − 24, 00

10

12

8

8

2

X :

3

4

5

6

7

Y

:

3

5

5

7

Me(X) = Me(Y ) = 5

V ar(X) = s 2 = 1

n

k

i=1

(x i x) 2 n i

X Y

X

x i s i

D.P.(X) = s = s 2 =

1

n

k

i=1

(x i x) 2 × n i

CV (X) =

s

x × 100

Kg m

CV 50% CV < 50%

X Y DP (X) = DP (Y ) = s = 2 = 1, 41

Km Km Km

Q 1 , Q 2 Q 3

Q 1 25% 75%

Q 2 50% 50%

Q 3 75% 25%

, D 9

1

D 1 , D 2 ,

L =

100 × n

k

L

k k esimo´

n

2

L L k esimo´ P k

P k

L k esimo´ L L + 1

L

L =

, 9

k

4

k

× n, k = 1, 2, 3 L = 10 × n, k = 1, 2,

Q 1 = P 25 Q 2 = P 50

Q 3 = P 75

D 1 = P 10 D 2 = P 20 D 9 = P 90

= Q 3 Q 1

= P 90 P 10

= (Q 3 Q 1 )/2

P k

k esimo´

1

M d

2 x m ´ in x max´

3

Q 1 M d = Q 2 Q 3

2 a

(x 1 , n 1 ), (x 2 , n 2 ),

, (x k , n k ).

i=1 k (x i x) × n i = 0

20

30

40

40 70

k

i=1

(x i x) 2 × n i =

k

i=1

x

2

i

n i

k

i=1 x i 2

n

=

k

i=1

x

2

i

n i nx 2

V ar(X) = s 2 = 1

n

k

i=1

x

2

i

n i x 2

A = {1000; 1001; 1002; 1003; 1004; 1005} B = {0, 1, 2, 3, 4, 5}

n

i

3 a

1 :

2 :

3 :

1 :

2 :

c

φ.

n A B n A n B A B n A f A

f A = n A

n .

0 f A 1;

f A = 1, A n

f A = 0, A n

A B f AB A B,

f AB = f A + f B .

P (A) , ,

(i) 0 P (A) 1;

(ii) P (Ω) = 1;

(iii) (A B = φ) P (A B)

P (A) + P (B) .

=

P (A) , P (A)

φ P (φ) = 0.

c P (A c ) = 1 P (A) .

P (A B)

=

P (A) + P (B)

P (A B) .

S

S S = {a 1 , a 2 ,

, a k }

A P (A) A = {a i } p i {a i }

p i

0, i = 1, 2,

,

k

p 1 + p 2 +

+ p k

= 1

A r 1 r k

 

A

= {a j1 , a j2 ,

,

a jr },

j1, j2,

,

jr r k

{a jr }

P(A) = p j1 + p j2 +

+ p jr .

a 1 , a 2 a 3 a 1 a 2 a 3 p 1 , p 2 p 3

, a k } P ({a k }

k S = {a 1 , a 2 ,

P({a k }) =

1

k .

S = {a 1 , a 2 ,

, a k } m m k)

P (A) = m

k .

p q p × q

(P (A B)) ,

P (A B) = P (A) P (B) .

A

P(A) =

B

P(B) =

B A P (A | B)

P(A | B) =

A B P (A | B) A B

P(A | B) = P(A P(B) B)

P (B) =

0

A = {(x 1 , x 2 ); x 1 + x 2 = 10} B

P (A), P (B), P (A | B) P (B | A)

= {(x 1 , x 2 ); x 1 > x 2 }

P(A | B) = P(AB)

P(B | A) = P(AB)

P(B)

P(A)

P(A B) = P(B)P(A | B)

P(A B) = P(A)P(B | A)

P (A 1 A 2 ∩ ··· ∩ A n ) = P (A 1 ) P (A 2 | A 1 ) P (A 3 | A 1 A 2 ) ··· P (A n | A 1 A 2 ∩ ··· ∩ A n1 )

A B A B A

P(A | B) = P(A).

A B B A

P(B | A) = P(B).

P(A B) = P(A)P(B)

P(A C) = P(A)P(C)

P(B C) = P(B)P(C)

P(A B C) = P(A)P(B)P(C)

S = {1, 2, 3, 4} A = {1, 2}; B = {1, 3}; C = {1, 4} S A, B C

B 1 , B 2 , S

, B k

B i B j = φ i

=

i=1 B i = S

P (B i ) > 0 i

k

j

A S B 1 , B 2 ,

, B k S

A = (A B 1 ) (A B 2 ) (A B 3 )

(A B k ).

P(A) = P(A B 1 ) + P(A B 2 ) + P(A B 3 ) +

+ P (A B k ).

P (A B j ) = P(B j )P(A | B j )

P(A) = P(B 1 )P(A | B 1 ) + P(B 2 )P(A | B 2 ) +

+ P (B k )P(A | B k ).

B i A

P(B i | A) = P(B P(A) i A)

=

P(B i )P(A | B i )

j P(B j )P(A | B j ) .

B i A B i A

3 a

N r (r < N )

P (B D)

P (A C)

x y z v

A B A B A B

¯

A B A B

A B C P (A B C) =

0 P (C | A B) =

P (C

| B) P (A | B C) = P (A | B)

1 5

A 3 B 4

2

3

 

A B C

4 a

S X s S X(s)

X

S X S R X B R X B R X A

A = {s S; X(s) B}

A B

B R X P (B) P (B) = P (A) A = {s S; X(s) B}

R X = {0, 1, 2, 3}

X X R X X

X

X R X X x 1 , x 2 ,

x i p(x i ) = P(X = x i ) x i p(x i ) i = 1, 2,

p(x i ) 0 i

Σ i=1 p(x i ) = 1

p X [x i , p(x i )] i = 1, 2,

4 4 X n

3

1

S =

P(X = n) =

X f f.d.p. X

f (x) 0 x

+

−∞

f (x)dx = 1,

a b −∞ < a < b < +, P (a X b) =

b f (x)dx.

a

X f.d.p. f

f(x) =

2x,

0,

0 < x < 1, c.c.

X f.d.p. X

f(x) =

kx,

0,

0 x 10 c.c

X F X F (x) = P (X x)

X

F(x) = p(x j ),

j

j x j x

X f.d.p. f

x

F(x) =

−∞

f (s)ds.

X F.d.a. X

X f.d.p.

f(x) =